(untitled) (BIRDEM Medical Journal, 2021)
Background: Sepsis is one of the most common admission-diagnosis in intensive care unit (ICU). It is associated with rapid organ dysfunction with increased mortality. Different scoring systems e.g. Sequential [Sepsis-related] Organ Failure Assessment (SOFA) score, systemic inflammatory response syndrome (SIRS) criteria are commonly used to identify and predict prognosis of sepsis in ICU at present. The objective was to determine the prognostic value of SOFA score and SIRS criteria among sepsis patients. Methods: This was a prospective observational study, conducted in the department of Critical Care Medicine, BIRDEM General Hospital during the period of January, 2018 to July, 2019. Consecutive sampling was conducted in patients fulfilling the selection criteria. After admission of patients with sepsis from indoor or emergency department; SOFA score and SIRS criteria were calculated using physiological and laboratory parameters recorded within 24 hours of ICU admission. Standard criteria were applied, an increase of point of e” 2 in SOFA score, and/ or SIRS criteria was regarded as sepsis. Patients who were admitted in ICU other than sepsis., known cases of acute myocardial infarction (MI), trauma victims, acute stroke, pregnancy, end stage renal disease (ESRD), decompensated chronic liver disease (CLD), who developed sepsis after admission in ICU, readmitted cases were excluded. All patients were followed up daily. Outcome was measured in terms of ICU mortality. Results: A total 203 patients were analyzed. About one-third (29.6%) patients belonged to age group 61-70 years (mean age: 58.25 ± 15.03 years); with slightly male predominance (52.2%). Pneumonia (56%) was the most common on admission diagnosis followed by uro-sepsis (19.7%). SOFA score showed greater discrimination (AUROC, 0.900 [95% CI, 0.860-0.941]) (p value <0.001) than SIRS criteria (AUROC,0.406 [95% CI, 0.327-0.486]). Conclusion: SOFA score had higher prognostic value than SIRS criteria regarding ICU mortality in sepsis. Birdem Med J 2021; 11(2): 84-89